Surface, Chemical, and Tribological Characterization of an ASTM F-1537 Cobalt Alloy Modified through an Ns-Pulse Laser - Cuao Moreu, Carlos Andrés; Maldonado Cortés, Demófilo; Lara Banda, María del Refugio; García Sánchez, Edgar O.; Zambrano Robledo, Patricia del Carmen; Hernández Rodríguez, Marco Antonio Loudovic (Molecular Diversity Preservation International, 2021)
Metallic biomaterials are considered safe materials for the fabrication of orthopedic prostheses due to their mechanical stability. Among this group, cobalt-chromium-molybdenum alloys are commonly used. Nevertheless, adverse reactions on tissues caused by the liberation of metallic ions are a limitation. Therefore, the modification of biometallic material surfaces has become a topic of interest, especially the improvement of the wear resistance to retard the degradation of the surface. In this work, dimples obtained at different processing parameters by an ns-pulse laser were texturized on an ASTM F-1537 cobalt alloy. Surfaces were characterized using scanning electron microscopy (SEM), energy dispersive spectroscopy, and Raman spectroscopy. The mechanical integrity of the surface was evaluated using a 3D surface analyzer and Vickers indentation tests. The tribological response was studied employing a ball-on-disc tribometer under lubricated conditions tracking the coefficient of friction, volume loss, wear rate, and surface damage by SEM. The variation of the laser power, repetition rate, and process repetitions slightly modified the chemistry of the surface (oxides formation). In addition, the rugosity of the zone treated by the laser increased. The texturized samples decreased the wear rate of the surface in comparison with the untreated samples, which was related to the variation of the dimple diameter and dimple depth.